Enhanced coarse-grained strategy for mixing process in high-solid content system - Yufan Bu; Xiangru Chen; Xiaofeng Wang; Liming Wang; Defu Che; Yulei Niu; Hai Nan (Chemical Engineering Journal, 2026)

Enhanced CO₂ decomposition by plasma-cold gas counter flow - Xianhui Chen; Runqi Liang; Defu Kong; Weidon Xia; Gang Pei; Xiangqian Wei (Journal of Environmental Chemical Engineering, 2026)

Structural disparity-driven heterogeneity in iron-catalyzed biomass pyrolysis: graphitization mechanisms of hemicellulose and lignin - Defu Shi; Chen Zhang; Sunwen Xia; Yingquan Chen; Haiping Yang (Fuel, 2026)

The discovery of natural-product inhibitors targeting white spot syndrome virus dUTPase (WSV112) through virtual screening and bioassays - Shangming Ran; Yuting Fu; Xiaolong Xue; Yueling Zhang; Defu Yao; Guanghui Chen (Aquaculture, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Acid-triggered degradation of a silicon-based nanopesticide activates SA-dependent conifer defense against Dioryctria sylvestrella - Zheng Wang; Antong Ma; Jiaxing Fang; Xiaoqi Xu; Wei Gan; Jiayue Liu; Fu Liu; Sufang Zhang; Defu Chi; Dafeng Chen; Yapei Wang; Xiangbo Kong (Pesticide Biochemistry and Physiology, 2026)

Multifactorial impacts on ash behaviors during oxy-fuel co-combustion of semi-coke and biomass - Jinping Zhang; Wenwen Wei; Haichen Zhao; Siyuan Li; Jingchun Shen; Defu Che; Lei Chen (Fuel, 2026)

Experimental study on in-situ pyrolysis of tar-rich coal under CO2 heating: tar-gas products extraction and microstructural evolution - Meijing Chen; Liujun Chang; Chang’an Wang; Tianlin Yuan; Mengjie Wu; Yujie Hou; Defu Che (Fuel, 2026)

Evaluation of stability and cooling engineering effectiveness of the Qinghai-Tibet transportation routes: A first comprehensive assessment using space geodetic observations - Lingxiao Wang; Lin Zhao; Shibo Liu; Huayun Zhou; Guojie Hu; Defu Zou; Erji Du; Guangyue Liu; Yao Xiao; Yueli Chen; Jianting Zhao; Wei Chen; et al. (Engineering Geology, 2026)

Two-phase structure matching strategy promotes formation of built-in electric fields in Eu-Co3O4/NiFe LDH heterojunction for anion exchange membrane water electrolysis - Wenjun Zhang; Xiaohui He; Jian Huang; Defu Chen (Chemical Engineering Journal, 2026)

Mito-boosting nanovesicle hydrogel dressing rescues hepatocyte bioenergetic insufficiency and promotes post-hepatectomy regeneration - Yixiao Pan; Le Ding; Tangansu Zhang; Changjie Yang; Huimin Wu; Xiandong Zeng; Yingqiang Liang; Defu Kong; Shihang Yu; Yiwen Chen; Siyuan Pan; Hongye Wang; et al. (Chemical Engineering Journal, 2026)

Metallic Contaminants and Osteoporosis: a Review of the Gut-Bone Axis - Yongjie Yang; Shuqi Yuan; Tianbao Gong; Jiaxiang Zhang; Haitao Ma; Defu Yu; Tao Chen (Biological Trace Element Research, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Research on the synergistic catalytic conversion of CO2 and its mechanism in a novel gliding arc plasma fluidized bed - Defu Kong; Xianhui Chen; Taohon Ye; Cheng Zhu; Haoxin Hu; Weidon Xia (Environmental Research, 2025)

Study on the mechanism of multiple sodium salts co-loading on ash fusibility and mineral evolution behaviors - Hongli Liang; Jinhao Yi; Yang Yang; Lei Zhang; Tao Ma; Weibin Chen; Hu Liu; Defu Che (Fuel, 2025)

Preparation of carbon nanosheet from molten salts assisted pyrolysis of biomass towards to carbon-negative technology - Sunwen Xia; Chen Zhang; Rui Fang; Yong Wang; Defu Shi; Bin Li; Dong Wang; Kuihua Han; Haiping Yang (Fuel, 2025)

Promising eco-friendly agents targeting Pseudomonas fluorescens biofilms - Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li; Lu Wang; Xue Bai (Food Bioscience, 2025)

Study on NO formation and ash characteristics during co-combustion of semi-coke and biomass under O2/CO2 conditions - Jinping Zhang; Jingchun Shen; Junyi Fang; Lei Chen; Chang’an Wang; Defu Che (Fuel, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

Study on characterization of tri-phase products and microstructure evolution during in-situ pyrolysis of tar-rich coal at different temperatures - Meijing Chen; Yongbo Du; Chang’an Wang; Tianlin Yuan; Yujie Hou; Liujun Chang; Lei Deng; Defu Che (Fuel, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

Effects of residual carbon on slag flow characteristics of Zhundong high-alkali coal under oxy-fuel condition - Yuanmao Chen; Chang’an Wang; Maoyun Luo; Lin Zhao; Pengbo Zhao; Defu Che (Fuel, 2025)

Targeted phytogenic compounds against Vibrio parahaemolyticus biofilms - Xue Bai; Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li (Critical Reviews in Food Science and Nutrition, 2025)

Experimental investigation on gas-liquid–solid tri-phase product distributions during the simulated in-situ pyrolysis of tar-rich coal - Meijing Chen; Chang’an Wang; Tianlin Yuan; Xing Ning; Xiaole Huang; Lei Deng; Defu Che (Fuel, 2025)

White spot syndrome virus IE1 protein blocks the integrin-FAK signaling to enhance viral infection in shrimp - Kaiyu Lu; Xiyu Chen; Huimin Zhang; Jinghua Zhu; Yongzhen Zhao; Xiuli Chen; Yueling Zhang; Defu Yao (Fish & Shellfish Immunology, 2025)

Cell Death in Crustacean Immune Defense - Zeyan Chen; Muhammad Tayyab; Defu Yao; Jude Juventus Aweya; Zhihong Zheng; Xianliang Zhao; Zhongyang Lin; Yueling Zhang (Reviews in Aquaculture, 2025)
Cell death mechanisms in crustaceans are a complex interplay of processes essential for maintaining cellular homeostasis and immune defense. Modes of cell death like apoptosis, necroptosis, and necrosis are well‐documented in crustaceans, serving crucial roles in removing damaged or infected cells. Unlike in other organisms, crustaceans likely lack pyroptosis, a type of programmed cell death associated with innate immunity and inflammation, because they do not possess the gasdermin genes essential for this process. Recently, NETosis and ferroptosis have emerged as significant mechanisms in pathogen defense. NETosis, involving the release of DNA fibers and antimicrobial proteins, helps trap and neutralize pathogens, while ferroptosis, an iron‐dependent form of cell death, contributes to lipid peroxidation and immune responses. Cuproptosis, although not yet studied in the context of crustacean immunity, shows potential crosstalk with ferroptosis, particularly in the regulation of metal ion homeostasis, oxidative stress, and cellular metabolism. Understanding these mechanisms offers promising applications in aquaculture, such as developing targeted immune modulators and enhancing disease resistance in economically important crustacean species.

Copper Homeostasis and Its Impact on Innate Immunity in Crustaceans - Hejia Chen; Xi Huang; Muhammad Tayyab; Mingming Zhao; Defu Yao; Zhihong Zheng; Xianliang Zhao; Yongzhen Zhao; Xiuli Chen; Bobo Zhang; Qiongqiong Yang; Yueling Zhang; et al. (Reviews in Aquaculture, 2025)
Copper, an essential micronutrient in crustaceans, plays vital roles in enzymatic processes, oxygen transport, pigmentation, and structural protein synthesis, including collagen and elastin. Recent research has elucidated its pivotal role in innate immunity of crustaceans, enhancing the immune response by promoting phagocytic activity, antimicrobial peptide production, and modulation of immune gene expression. Copper ions exhibit antimicrobial effects by disrupting cell membranes and inhibiting microbial proliferation. Furthermore, copper governs antioxidant defense mechanisms, protecting crustaceans against oxidative stress and infection. However, excessive copper can lead to toxicity, highlighting the need for strict maintenance of copper homeostasis. This review explores the complex processes of copper homeostasis in crustaceans, detailing transport mechanisms, storage proteins, and detoxification pathways. It emphasizes copper's critical physiological and immunological functions, contributing to a comprehensive understanding of its multifaceted roles in crustaceans and laying groundwork for further exploration of copper homeostasis as a strategy for boosting crustacean immunity. Aquaculture practices significantly influence copper levels in crustaceans. Effective copper management, including monitoring techniques, water treatment strategies, and regulatory frameworks, is crucial for both crustacean welfare and environmental sustainability.

Preparation of a slow-release fertilizer from MgO-modified biochar and struvite and its capacity for cadmium passivation - Zanmei Chen; Defu Xu; Die Wu; Tingtian Lu; Alan Howard (Journal of Environmental Chemical Engineering, 2024)

Experimental study and chemical equilibrium calculation on the mineral transformation of high-alkali coal under oxy-fuel condition - Lin Zhao; Chang’an Wang; Yingchao Nie; Yongxu Chen; Jinming Zhang; Maoyun Luo; Defu Che (Fuel, 2024)

Progress in phosphorylation of natural products - Xiaoran Mao; Jiaqi Chen; Yingrui Yao; Defu Liu; Haiying Wang; Yuzhou Chen (Molecular Biology Reports, 2024)

Microbial communities associated with the mature sporophytes and sporelings of the commercially cultivated seaweed Saccharina japonica in Southern China - Yingrui Zhuang; Mahasweta Saha; Yan Bai; Suhelen Egan; Yixiao Han; Qiying Qiu; Defu Chen; Gaoge Wang (Journal of Applied Phycology, 2024)

Chemical kinetics simulation on nitrogen migration characteristics during co-combustion of ammonia and coal under deeply fuel-air multistage conditions - Liangxu Dai; Chang’an Wang; Yujie Hou; Guowei Ma; Yongxu Chen; Abu Hurera; Lei Zhou; Defu Che (Fuel, 2024)

Self-supporting electrodes for high-performance flexible solid-state supercapacitors: Recent advances and perspectives - Yanxin Liao; Defu Tang; Shile Liu; Tianrui Liu; Lingyun Chen; Qichun Zhang (Chemical Engineering Journal, 2024)

Methane dynamics altered by reservoir operations in a typical tributary of the Three Gorges Reservoir - Jia Liu; Fei Xue; Xiaojuan Guo; Zhengjian Yang; Manchun Kang; Min Chen; Daobin Ji; Defu Liu; Shangbin Xiao; Chenghao Wang (Water Research, 2024)

OsIPK1 frameshift mutations disturb phosphorus homeostasis and impair starch synthesis during grain filling in rice - Lina Wang; Jing Cui; Ning Zhang; Xueqin Wang; Jingping Su; María Pilar Vallés; Shian Wu; Wei Yao; Xiwen Chen; Defu Chen (Plant Molecular Biology, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Efficient synthesis of furfural over mZSM-5@SO42-/mSiO2 core–shell catalyst by targeted regulating B/L acids - Renjie Ji; Defu Yin; Yao Chen; Like Ma; Fanglin Lv; Yuhao Zhang; Zhen Jia; Jingyun Zhang; Mingya Liu; Shitao Yu; Yue Liu (Fuel, 2024)

Electric-field-controlled energy barrier and reaction pathway ensure high sulfur product selectivity in Cu/γ-Al2O3 catalyst-assisted DBD plasma conversion of carbonyl sulfide - Yixing Ma; Peng Chen; Defu Li; Fei Wang; Langlang Wang; Kai Li; Ping Ning; Xueqian Wang; Kostya (Ken) Ostrikov (Journal of Environmental Chemical Engineering, 2024)

Exploring the link between microbial community structure and flavour compounds of traditional fermented yak milk in Gannan region - Hongqiang Li; Xiaoling Yang; Defu Tang; Bin Xi; Weihong Li; Zhaohui Chen; Yongqing Bao; Renqing Dingkao; Yaqin Gao; Peng Wang; Hongbo Wang (Food Chemistry, 2024)

The evolutionary adaptation of shrimp hemocyanin subtypes and the consequences on their structure and functions - Jiaxi Li; Mingming Zhao; Xin Zhang; Zhihong Zheng; Defu Yao; Shen Yang; Ting Chen; Yueling Zhang; Jude Juventus Aweya (Fish & Shellfish Immunology, 2024)

Preparation of a coagulant of polysilicate aluminum ferric from foundry dust and its coagulation performance in treatment of swine wastewater - Junhong Yi; Zanmei Chen; Defu Xu; Die Wu; Alan Howard (Journal of Cleaner Production, 2024)

Penaeid shrimp counteract high ammonia stress by generating and using functional peptides from hemocyanin, such as HMCs27 - Mingming Zhao; Zhihong Zheng; Chuanqi Wang; Defu Yao; Zhongyang Lin; Yongzhen Zhao; Xiuli Chen; Shengkang Li; Jude Juventus Aweya; Yueling Zhang (Science of The Total Environment, 2023)

Investigation on Co-combustion characteristics and NO emissions of coal and municipal sludge in a tangentially fired boiler - Chang'an Wang; Meijing Chen; Pengbo Zhao; Lei Zhou; Yujie Hou; Jinming Zhang; Qiang Lyu; Defu Che (Fuel, 2023)

An opportunistic pathogenic Pseudomonas isolated from healthy brown alga Saccharina japonica - Qin Yang; Yingrui Zhuang; Mahasweta Saha; Qiying Qiu; Defu Chen; Lirong Chang; Luyang Xiao; Gaoge Wang (Aquaculture, 2023)

Microfiber-loaded bacterial community in indoor fallout and air-conditioner filter dust - Yingxin Chen; Xinyu Li; Wei Gao; Yalin Zhang; Aoyun Mo; Jie Jiang; Defu He (Science of The Total Environment, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Prominent toxicity of isocyanates and maleic anhydrides to Caenorhabditis elegans: Multilevel assay for typical organic additives of biodegradable plastics - Xinyu Li; Yingxin Chen; Wei Gao; Aoyun Mo; Yalin Zhang; Jie Jiang; Defu He (Journal of Hazardous Materials, 2023)

Receptor-like kinase HAESA-like 1 positively regulates seed longevity in Arabidopsis - Defu Chen; Hongye Guo; Shuai Chen; Qianying Yue; Pei Wang; Xiwen Chen (Planta, 2022)

Crop pest recognition using attention-embedded lightweight network under field conditions - Junde Chen; Weirong Chen; Adnan Zeb; Defu Zhang; Yaser Ahangari Nanehkaran (Applied Entomology and Zoology, 2021)

Isolation and identification of a pathogenic bacterium, Exiguobacterium oxidotolerans XP-2, from the abnormal diseased mature sporophytes of a commercially cultivated brown seaweed Saccharina japonica - Rafiq Ahmad; Yao Chen; Yingrui Zhuang; Qiying Qiu; Defu Chen; Mahasweta Saha; Hongyan Wu; Gaoge Wang (Journal of Applied Phycology, 2021)

Effects of Chronic Stress on the Fecal Microbiome of Malayan Pangolins (Manis javanica) Rescued from the Illegal Wildlife Trade - Dingyu Yan; Defu Hu; Kaixiang Li; Baocai Li; Xiangyan Zeng; Jinyan Chen; Yimeng Li; Torsten Wronski (Current Microbiology, 2021)

Enhanced dewater efficiency for river sediment by top-to-bottom water transmitting channels with different materials - Zhuo Shi; Kewu Pi; Xuanming Huang; Yafei Shi; Ziwen Chen; Ruyu Tang; Zehui Hu; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2020)

In-depth proteomic profiling of the Singapore grouper iridovirus virion - Defu Yao; Yingfu Liu; Xiuli Chen; Teck Kwang Lim; Lili Wang; Jude Juventus Aweya; Yueling Zhang; Qingsong Lin (Archives of Virology, 2019)

Specific roles of Os4BGlu10, Os6BGlu24, and Os9BGlu33 in seed germination, root elongation, and drought tolerance in rice - Ruijuan Ren; Dong Li; Chunyan Zhen; Defu Chen; Xiwen Chen (Planta, 2019)

Filtered maximum likelihood expectation maximization based global reconstruction for bioluminescence tomography - Defu Yang; Lin Wang; Dongmei Chen; Chenggang Yan; Xiaowei He; Jimin Liang; Xueli Chen (Medical & Biological Engineering & Computing, 2018)

Isolation, Immobilization, and Degradation Performance of the 17β-Estradiol-Degrading Bacterium Rhodococcus sp. JX-2 - Jingxian Liu; Juan Liu; Defu Xu; Wanting Ling; Shunyao Li; Mindong Chen (Water, Air, & Soil Pollution, 2016)

Performance investigation of SP3 and diffusion approximation for three-dimensional whole-body optical imaging of small animals - Defu Yang; Xueli Chen; Xu Cao; Jing Wang; Jimin Liang; Jie Tian (Medical & Biological Engineering & Computing, 2015)

The change of organic matter in sewage sludge composting and its influence on the adsorption of pentachlorophenol (PCP) - Lou Liping; Liu Defu; Chen Huanyu; Chen Fang; He Yunfeng; Tian Guangming (Environmental Science and Pollution Research, 2015)

Toxicity bioassays for water from black-odor rivers in Wenzhou, China - He DeFu; Chen RuiRui; Zhu EnHui; Chen Na; Yang Bo; Shi HuaHong; Huang MinSheng (Environmental Science and Pollution Research, 2015)

Juvenile silver carp Hypophthalmichthys molitrix swim faster in closed surface flow than open surface flow - Xiaotao Shi; Qiuwen Chen; Defu Liu; Yingping Huang; Ping Zhuang; Bo Lu (Environmental Biology of Fishes, 2014)

Tocopherol-deficient rice plants display increased sensitivity to photooxidative stress - Defu Chen; Haiwei Chen; Luhua Zhang; Xiaoli Shi; Xiwen Chen (Planta, 2014)

Identification and Characterization of Human MIBP1 Gene in Glioma Cell Differentiation - Lijun Sun; Xiwen Chen; Xingnan Jin; Qiang Huang; Weilan Wang; Dashi Zhi; Defu Chen (Journal of Molecular Neuroscience, 2014)

Transmembrane routes of cationic liposome-mediated gene delivery using human throat epidermis cancer cells - Shaohui Cui; Bing Wang; Yinan Zhao; Huiying Chen; Huiqin Ding; Defu Zhi; Shubiao Zhang (Biotechnology Letters, 2014)

Feasibility Study on Quantitative Measurements of Singlet Oxygen Generation Using Singlet Oxygen Sensor Green - Huiyun Lin; Yi Shen; Defu Chen; Lisheng Lin; Brian C. Wilson; Buhong Li; Shusen Xie (Journal of Fluorescence, 2013)

Knockdown of ZNF403 inhibits cell proliferation and induces G2/M arrest by modulating cell-cycle mediators - Rui Guan; Xiao-Yan Wen; Jing Wu; Rongqi Duan; Huibi Cao; Simon Lam; Defu Hou; Youdong Wang; Jim Hu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2012)

Cloning and characterization of the NPCEDRG gene promoter - Defu Hou; Yongjun Guan; Jianping Liu; Zhefeng Xiao; Yongmei Ouyang; Yanhui Yu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2011)

Transgenic tobacco plants expressing atzA exhibit resistance and strong ability to degrade atrazine - Huizhuan Wang; Xiwen Chen; Xuguang Xing; Xiaohua Hao; Defu Chen (Plant Cell Reports, 2010)

Analysis of Diversity in Chinese Cultivated Barley with Simple Sequence Repeats: Differences Between Eco-Geographic Populations - Feixue Chen; Defu Chen; María-Pilar Vallés; Zhen Gao; Xiwen Chen (Biochemical Genetics, 2010)

Assessing Genetic Diversity of Chinese Cultivated Barley by STS Markers - Xiwen Chen; Shaoying Guo; Defu Chen; Pin Liu; Xiangdong Jia; Lijun Sun (Genetic Resources and Crop Evolution, 2006)

A preliminary study of trace elements in plasma protein by gel chromatography combined with SXRF - Nianqing Liu; Plngsheng Liu; Kongjiang Wamg; Defu Chen; Jinyuan Zhao; Qing Xu (Biological Trace Element Research, 1999)